Student admission into higher education system: case study of Psychology career of "Universidad Internacional SEK" Ecuador - Ramos, Carlos (2017)
Student admission process in private high er education system determines the maintenance of diff erent college career off er. In this context, in this article a research that analyzed the current state of admission of students in the psychology of the SEK International University of Ecuador is reported. The method used in the research was a mixed type, in which a first quantitative phase evaluated socio demographic variables related to income students. In this stage, students answered a qualitative instrument. We worked with 100% of psychology students (23 women and 8 men). As a result of research variables related to the educational level of parents, school income, prepaid values and subjective constructions related to the current situation of the psychology are identified. The results are discussed in reference to the future steps to be done in order to improve the situation of admissions that was analyzed.